2019
DOI: 10.1002/ajim.23054
|View full text |Cite
|
Sign up to set email alerts
|

Night work is related to higher global and central adiposity in Brazil: National Health Survey, 2013

Abstract: Background: Night work can disturb the natural circadian rhythm, leading to disruptions in metabolic rate and subsequent overall gain weight or even more harmful abdominal adiposity. Our aims were to investigate the associations between night work frequency and markers of overall and central obesity.Methods: We conducted a cross-sectional analysis of data from the Brazilian National Health Survey on over 35 500 current workers. Exposure to current night work was composed of three categories: daytime work (refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Metabolic syndrome (MS), with globally increasing prevalence, is characterised by a set of cardiovascular risk factors, such as abdominal obesity, insulin resistance, hypertension, impaired glucose metabolism, and dyslipidaemia. It is an example of a non‐infective syndrome caused by modern life habits 3‐8 . Its multisystemic pattern is due to a pro‐inflammatory state, oxidative stress, haemodynamic dysfunction, and ischaemia, which overlap in ‘dysmetabolic’ patients.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome (MS), with globally increasing prevalence, is characterised by a set of cardiovascular risk factors, such as abdominal obesity, insulin resistance, hypertension, impaired glucose metabolism, and dyslipidaemia. It is an example of a non‐infective syndrome caused by modern life habits 3‐8 . Its multisystemic pattern is due to a pro‐inflammatory state, oxidative stress, haemodynamic dysfunction, and ischaemia, which overlap in ‘dysmetabolic’ patients.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding central adiposity, unlike the current study, some studies found central adiposity had a significant (but sometimes marginal) association with night shift work. 9 , 28 , 38 , 39 Conflicting results could be due to variation in the methods of studies, for example, Antunes et al study included a considerably small sample size (14 shift workers and 13 daytime workers). 38 In Sun et al study, the cut-off point of central adiposity was set according to the recommended criteria for Chinese populations (waist circumference ≥85 cm for men).…”
Section: Discussionmentioning
confidence: 99%
“… 38 In Sun et al study, the cut-off point of central adiposity was set according to the recommended criteria for Chinese populations (waist circumference ≥85 cm for men). 28 Correia et al study had a different study design, 9 and Ulacia et al study evaluated adiposity in a specific working population (nursing workers). 39 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations